2022
DOI: 10.1021/acs.chemrev.1c00905
|View full text |Cite
|
Sign up to set email alerts
|

Designing Sites in Heterogeneous Catalysis: Are We Reaching Selectivities Competitive With Those of Homogeneous Catalysts?

Abstract: A critical review of different prominent nanotechnologies adapted to catalysis is provided, with focus on how they contribute to the improvement of selectivity in heterogeneous catalysis. Ways to modify catalytic sites range from the use of the reversible or irreversible adsorption of molecular modifiers to the immobilization or tethering of homogeneous catalysts and the development of well-defined catalytic sites on solid surfaces. The latter covers methods for the dispersion of single-atom sites within solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
121
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(121 citation statements)
references
References 2,270 publications
0
121
0
Order By: Relevance
“…71−73 Specifically, for cyano-containing compounds (mostly, higher mass organic molecules), a large body of experimental work was previously published, in which the combination of long-and short-range interactions was put forward to explain the experimental results. 28,31,56−61 Thus, Gottardi et al 57 observed a hexagonal closed-packed phase forming upon the adsorption of a triarylamine derivate 4,4,8,8,12,12-hexamethyl-4H,8H,12H-benzo [1,9]quinolizino- [3,4,5,6,7-defg]acridine-2,6,10-tricarbonitrile on Au(111). The authors explained the experimentally observed patterns by a combination of (i) long-range attractive dipolar coupling of the terminal CN-groups of two adjacent molecules (CN•••CN bond) and (ii) short-range hydrogen bonding between the nitrogen atom of the CN-group and an H atom of the phenyl ring in close proximity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…71−73 Specifically, for cyano-containing compounds (mostly, higher mass organic molecules), a large body of experimental work was previously published, in which the combination of long-and short-range interactions was put forward to explain the experimental results. 28,31,56−61 Thus, Gottardi et al 57 observed a hexagonal closed-packed phase forming upon the adsorption of a triarylamine derivate 4,4,8,8,12,12-hexamethyl-4H,8H,12H-benzo [1,9]quinolizino- [3,4,5,6,7-defg]acridine-2,6,10-tricarbonitrile on Au(111). The authors explained the experimentally observed patterns by a combination of (i) long-range attractive dipolar coupling of the terminal CN-groups of two adjacent molecules (CN•••CN bond) and (ii) short-range hydrogen bonding between the nitrogen atom of the CN-group and an H atom of the phenyl ring in close proximity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The authors explained the experimentally observed patterns by a combination of (i) long-range attractive dipolar coupling of the terminal CN-groups of two adjacent molecules (CN•••CN bond) and (ii) short-range hydrogen bonding between the nitrogen atom of the CN-group and an H atom of the phenyl ring in close proximity. Stoḧr et al 31 showed the formation of fully segregated domains of pure enantiomers formed upon adsorption of the racemic mixture of 6,13-dicyano [7]helicene on Cu(111). As a driving force for the chiral recognition in enantiopure domains, the authors put forward a combination of (i) short�range hydrogen bonding between an aromatic hydrogen atom and the adjacent CN-group of another molecule and (ii) long-range attractive CN•••CN dipolar coupling.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two or more metal centers synergically act in the active site of several enzymes, thus improving kinetics and imparting high selectivity [1,2]. Based on this mechanism of action, multinuclear cooperative catalysis has been applied to many processes, including coordination polymerization, olefin hydrogenation, hydroformylation, cycloaddition, and epoxidation [3][4][5]. In olefin polymerization reactions catalyzed by multinuclear transition metal complexes, cooperative effects significantly enhance the molecular weight, chain branch density, and comonomer enchainment selectivity of the products compared to the reactions catalyzed by analogous mononuclear catalysts [6,7].…”
Section: Introductionmentioning
confidence: 99%